Present and Future Trends in Translation Studies - Haru Deliana Dewi (Deskripsi Bahasa, 2018)
Translation Studies is a relatively new discipline in the world, and in Indonesia it is not much heard of, let alone studied by. Moreover, none of the universities in this country has Translation Studies as one of its study programs or departments. Translation is still considered part of a linguistics department or literature department. Thus, this paper will explain this ‘new’ discipline, what it covers, and the trends it has in the present and future times. It is expected that this paper will be an eye-opener for many academicians in Indonesia to be aware of Translation Studies as an independent discipline which draws from many disciplines and to encourage people to learn more about this discipline.